Aging Effect on Functionalized Silver-Based Nanocoating Braided Coronary Stents - Rebelo, Rita (2020)
A previously developed fiber-based polyester (PES) stent, with mechanical properties comparable to commercial nitinol stents, was coated with metallic silver (Ag0) and silver oxides (AgxO) thin films through direct current (DC) magnetron sputtering. Ag0 and AgxO coatings provide antimicrobial properties to the stents to minimize the occurrence of coronary stent infections. Nevertheless, the stent interacts with the atmosphere and then with the biological fluids and may lead to the generation of silver species with diminished antimicrobial e ciency and/or prone to induce cytotoxicity. Therefore, stent coating nanostructures aged 3 months were thoroughly analyzed by X-ray photoelectron spectroscopy (XPS) and their antimicrobial and cytotoxicity properties were assessed. Aging led to the presence of silver carbonate and bicarbonate as well as chemisorbed oxygen species in Ag0 and AgxO coatings. Bactericidal e cacy was tested against an important nosocomial bacterium, particularly associated to indwelling devices: Staphylococcus epidermidis. Aged Ag0 and AgxO coating presented a Log reduction of 1 and 2 at their surface; respectively. However, aged stents were able to induce a Log reduction of 2 (Ag0) and 4 (AgxO) on the surrounding medium. Only aged AgxOstent was able to provide a mild reduction of the bacterium at its surface and a clear antimicrobial e ect (Log reduction >3) within its vicinity. More importantly, both aged Ag0 and AgxO stents were shown to be compatible with fibroblasts cells indicating that they can be safely used as indwelling devices, despite the aging e ect.